2020
DOI: 10.37897/rjn.2020.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Complications as poor prognostic factors in patients with hemorrhagic stroke: A hospital-based stroke registry

Abstract: Introduction. Stroke patients commonly experience various medical complications during their rehabilitation stay. Understanding complications in hemorrhagic stroke patients can determine the patients prognosis. Aim. This study aimed to explore complications as prognostic factors among patients with hemorrhagic stroke. Methods. This was an observational analytic study with retrospective design. We analyzed the medical records of 480 patients admitted with hemorrhagic stroke between 2017 and 2018 at Bethesda Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
2
1
0
2
Order By: Relevance
“…This prospective cohort study was conducted among stroke patients in Northwest Ethiopia to identify the 28 days follow-up case fatality rate and its determinants among admitted stroke patient. On a 28-day follow-up, 27.08% of patients have died which was comparable with a studies from Ethiopia (29.3%) (30.1%), and Uganda (26.8%) (15,19,20). However, the rate was…”
Section: Comparison With Literaturessupporting
confidence: 85%
“…This prospective cohort study was conducted among stroke patients in Northwest Ethiopia to identify the 28 days follow-up case fatality rate and its determinants among admitted stroke patient. On a 28-day follow-up, 27.08% of patients have died which was comparable with a studies from Ethiopia (29.3%) (30.1%), and Uganda (26.8%) (15,19,20). However, the rate was…”
Section: Comparison With Literaturessupporting
confidence: 85%
“…Research by Ramdani (2018) shows that the first recurrence in the >12 months period was 45.2%, in the 7-12 months period 41.1%, and 31.7% of respondents experienced a recurrence <6 months. Another study confirmed that 1 out of 10 stroke survivors had stroke recurrence within 6-12 months of the first stroke (Pinzon and Vijaya, 2020). The results of our study show that there is an association between the prevalence of stroke recurrence and cognitive function.…”
Section: Association Between Stroke Recurrence and Cognitive Functionsupporting
confidence: 83%
“…The majority of respondents experienced the first recurrence, with the largest type of stroke being ischemic. According to a prior study, patients with ischemic stroke (63.3%) experience recurrence more frequently than those with hemorrhagic stroke (Pinzon and Vijaya, 2020). According to a systematic review, stroke survivors had a higher prevalence of stroke recurrence (33%) than those with hemorrhagic stroke (26.3%) (Rao et al, 2016).…”
Section: Association Between Stroke Recurrence and Cognitive Functionmentioning
confidence: 99%
“…[22,23] Sementara itu, pasien dengan stroke hemoragik cenderung untuk mengalami komplikasi berupa perdarahan saluran cerna. [24] Komplikasi yang terjadi di rumah sakit dapat berupa infeksi maupun non infeksi. Komplikasi terkait infeksi dapat berupa pneumonia dan infeksi saluran kemih.…”
Section: Pembahasanunclassified
“…[25] Peningkatan tekanan intrakranial dapat menginduksi hiperaktivitas dari vagus yang berakibat pada iskemia dari mukosa serta peningkatan asam lambung, hal tersebut dapat menyebabkan komplikasi berupa perdarahan saluran cerna atau stress ulcer. [24] Hasil analisis menunjukkan bahwa terdapat hubungan antara jenis stroke terhadap lama perawatan rawat inap pada pasien stroke. Analisis multivariat juga menunjukkan hal serupa, stroke hemoragik merupakan faktor risiko lama perawatan rawat inap >7 hari.…”
Section: Pembahasanunclassified